PENURUNAN FUNGSI FISIK DAN DUKUNGAN KELUARGA DENGAN GANGGUAN PSIKOSOSIAL PADA LANJUT USIA (LANSIA)DI KELURAHAN PILOLODAA KECAMATAN KOTA BARAT KOTA GORONTALO - Firmawati Firmawati; Lenny Ali; Sitti Nur Fajirin Tahir (Universitas Muhammadiyah Gorontalo, 2020)
The decrease in physical function has an impact on psychosocial disorders in the elderly, this can be overcome by increasing family support. The purpose of this researcy is to determine the correlation of decreased physical function and family support with psychosocial disorders in the elderly. This research method uses survey-analytic with cross-sectional approach. The population in this study were all the elderly who lived in the Piloloda Village with a sample of 55 elderly and the sampling technique used purposive sampling and analyzed with the chi square test. The results indicates that the majority of the elderly's physical function decreased by 69.1%, 80% less family support, and 76.4% less psychosocial disorders with a significant p = 0,000 <α = 0.05. it is concluded that there is a correlation of decreased physical function with psychosocial disorders in the elderly and there is a correlation of family support with psychosocial disorders in the elderly.